Safavid Knowledge Tradition for Science Integration in Islamic Education - Amelia Widjastuti; Iin Kandedes; Zaimudin Zaimudin (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The Safavid civilization represents one of the most significant periods in Islamic history, making substantial contributions to the advancement of knowledge through the integration of religious sciences and rational sciences. This study aims to analyze the contributions of the Safavid civilization to the development of knowledge and to examine its implications for the integration of science within Islamic education. Employing a qualitative approach through library research, the study draws upon data collected from books, scholarly journals, and other relevant academic sources. The data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that scientific and intellectual progress during the Safavid era was supported by governmental policies, the establishment of madrasas and libraries, and the patronage provided to scholars and intellectuals. These developments fostered significant achievements in philosophy, astronomy, mathematics, medicine, art, architecture, and calligraphy. Furthermore, the Safavid intellectual tradition successfully integrated reason, revelation, and spiritual intuition, particularly through the philosophical thought of Mulla Sadra, thereby preventing a dichotomous separation between religious and secular knowledge. This study demonstrates that the Safavid intellectual tradition provides a historical and epistemological foundation for the contemporary paradigm of science integration by illustrating how the harmonious relationship between religious and rational sciences can address the persistent dichotomy of knowledge in Islamic education. The findings indicate that the Safavid model of scholarship is not only historically significant but also practically applicable to the development of integrative curricula, interdisciplinary learning approaches, the strengthening of research culture, and educational practices that balance scientific competence with Islamic values. This research contributes a historical perspective on knowledge integration as an alternative framework for addressing the persistent dichotomy of knowledge in contemporary Islamic education.